1993
DOI: 10.2134/jeq1993.00472425002200040005x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Daily Nutrient Fluxes to a Large Piedmont Reservoir from Limited Tributary Data

Abstract: Physically based models of lakes require estimates of daily, spatially varied water and nutrient fluxes into the lake from surrounding watersheds. Often, however, only a selected set of streams are periodically (monthly or biweekly) sampled. The objective of this study was to develop and test a method for estimating daily flux of nutrients into a large reservoir using data from sampling of selected watersheds. Flow rate, nitrate (NO3‐N), total nitrogen (TN), soluble reactive phosphorus (SRP), total phosphorus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Several other studies have found that discharges of N and often P increase as the proportion of agricultural land increases (Hill, 1978;Neill, 1989;Mason et al, 1990;Dillon and Kirchner, 1975;Rekolainen, 1990;Correll et al, 1992;Nearing et al, 1993), but some studies have found no apparent effect of agricultural land use on N and P discharge (Owens et al, 1991;Thomas et al, 1992). Since P discharge is related to transport of suspended particles, the influence of agriculture on P discharge may be outweighed by the effects of the geochemistry and erodibility of sediments in the watershed (Grobler and Silberbauer, 1985;Vighi et al, 1991;Dillon and Kirchner, 1975;Rekolainen, 1 990).…”
Section: Nitrogen and Phosphorus Dischargesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have found that discharges of N and often P increase as the proportion of agricultural land increases (Hill, 1978;Neill, 1989;Mason et al, 1990;Dillon and Kirchner, 1975;Rekolainen, 1990;Correll et al, 1992;Nearing et al, 1993), but some studies have found no apparent effect of agricultural land use on N and P discharge (Owens et al, 1991;Thomas et al, 1992). Since P discharge is related to transport of suspended particles, the influence of agriculture on P discharge may be outweighed by the effects of the geochemistry and erodibility of sediments in the watershed (Grobler and Silberbauer, 1985;Vighi et al, 1991;Dillon and Kirchner, 1975;Rekolainen, 1 990).…”
Section: Nitrogen and Phosphorus Dischargesmentioning
confidence: 99%
“…Watersheds with greater proportions of agricultural land have been found to discharge greater amounts of N (Hill, 1978;Neill, 1989;Mason et al, 1990), P (Dillon and Kirchner, 1975), or both nutrients (Rekolainen, 1990;Correll et al, 1992;Nearing et al, 1993). Such observations have led to the derivation of nutrient export coefficients for particular land use types, such as croplands, pastures, and forests (Beaulac and Reckhow, 1982).…”
mentioning
confidence: 99%
“…A large amount of disposed N associated with human activities has been reported to affect river water quality, with sewage treatment plants in urban settlements as major point sources (Nearing et al 1993;O'Dell 1994;Nagumo and Hatano 2000). This study revealed that in the effluent of the landfill site, to which municipal wastes including sewage sludge generated in an urban area were imported, the T-N concentration was as high as 96-162 mg L -I, and resulted in a large increase in the T-N concentration and load.…”
Section: Discussionmentioning
confidence: 99%
“…Nearing et al (1993) estimated that, in the drainage basin of Lake Lanier, northern Georgia, US, the discharge from the sewage treatment plant contributed to 24% of the total N (T-N) load, compared to the agricultural contribution of 28%. O'Dell (1994) showed that the stream N loads before and after the removal of N discharge from the sewage treatment plant were 1,292 and 782 g S-I respectively, and the contribution of sewage drainage to the T-N load was estimated to be 39%.…”
mentioning
confidence: 99%
“…In these years, studies on the sources, cycling process and influencing factors of nitrate in surface water and groundwater bodies have been discussed. The studies demonstrated that the factors such as discrepancy of soil utilizing styles, the seasonally change of precipitation have evident discrepancy [4][5][6][7][8]. And other factors such as the depth of groundwater level, the thickness of unsaturated zone and the dynamic relationship influence the spatial distribution of nitrate pollution in groundwater bodies [9][10][11].…”
Section: Introductionmentioning
confidence: 99%